BEST PRACTICE PROGRAMME IN THE STANDARDISATION OF TRADITIONAL MEDICINES: EVALUATION OF AN IMMUNE BOOSTER FORMULATED BY TRADITIONAL HEALERS OF THE VAAL TRIANGLE, SOUTH AFRICA - Pinkoane, M.G.; Ngcobo, M.; Gqaleni, N. (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Regulation and standardization of African traditional medicines (ATM) prescribed by traditional healers in South Africa is still far from being implemented. This is despite the fact that more people are using ATM products than ever. In an effort to demonstrate that collaboration with traditional health practitioners (THPs) can yield standardized TM products, this study aimed to evaluate the immunomodulatory effects of an herbal immune booster formulated by traditional healers from the Vaal Region, South Africa. Materials and Methods: Using normal and lipopolysaccharide (LPS) stimulated human peripheral blood mononuclear cells (PBMCs) models, doses of the immune booster ranging from 1000 to 10 μg/mL were evaluated for their cytotoxicity, inflammatory cytokines and chemokines secretion, nitric oxide (NO) secretion, malondialdehyde (MDA) assay, and 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay. Results: The immune booster induced a dose dependent cytotoxic effect on both normal and LPS stimulated PBMCs with higher doses showing cytotoxicity while lower dose from 100μg/mL did not show any cytotoxicity. When re-dissolved in aqueous PBS immune booster doses up to 100 μg/mL showed better DPPH radical inhibition (41%) than ascorbic acid at 40μg/mL (33%). The immune booster also decreased lipid peroxides significantly (p< 0.05) and this was comparable to ascorbic acid. There was also a significant (p< 0.05) increase in nitrite (NO) after treatment of LPS stimulated PBMCs with immune booster doses when compared to untreated samples. The immune booster stimulated inflammatory cytokines secretion in normal PBMCs (IL 1α, IL 1β, IL 6, IL 10 and TNFα while showing a decrease in IFNγ at the higher dose) while in LPS stimulated PBMCs some cytokines were decreased (IL 1α, IL 17α and at lower doses IL 10 and TNFα) and others were increased (IFNγ, TNFα and GM-CSF) depending on the dose used. In both normal and LPS stimulated PBMCs the immune booster significantly (p< 0.05) increased (MIP 1α) while causing significant (p< 0.05) decreases in IP 10 (high dose), I-TAC and MIG secretion. Conclusions: This immune booster showed potential immunostimulatory effects by increasing nitric oxide, inflammatory cytokines and chemokines secretion in both normal and LPS stimulated PBMCs. This TM also showed promising antioxidant potential in the MDA and DPPH assays. Further in vitro and animal studies are warranted.